Examining the Chelating Effectiveness of Dimercaptosuccinic Acid and Ethylenediaminetetraacetic acid Calcium Disodium in Patients with Lead Poisoning : An Evidence-Based Case Report - Alfares, Heru; Rafsanzani, Reza A; Mansyur, Muchtaruddin (UI Scholars Hub, 2023)
Evidence Based Case Report: Examining the Chelating Effectiveness of Dimercaptosuccinic Acid and Ethylenediaminetetraacetic acid Calcium Disodium in Patients with Lead Poisoning Heru Alfares1, Reza A. Rafsanzani1, Muchtaruddin Mansyur2 1 Occupational Medicine Specialist Study Program, Faculty of Medicine, Universitas Indonesia, Jakarta, 2 Dept. of Community Medicine, Faculty of Medicine, Universitas Indonesia, Jakarta, ABSTRACT Background: Lead environmental and occupational exposures harm workers’ health, both acute and chronic lead poisoning. Chelation therapy is one of the treatments for lead poisoning using several chelating agents available, including ethylenediaminetetraacetic acid (EDTA), dimercaptosuccinic acid (DMSA), dimercaptopropanesulfonate (DMPS), and 2,3-dimercaptopropanol or British Anti Lewisite (BAL). However, the use of these chelating agents varies and lacks standardised guidelines for lead poisoning cases. Objective: To determine whether DMSA can be a better chelating agent than EDTA in treating lead poisoning among workers. Methods: This study conducted a literature search using evidence-based databases focusing on clinical questions using the “PICO” method. The author searched the relevant articles using the following databases: “PubMed,” “Cochrane Library,” and “EMBASE.” The keywords used included “lead poisoning,” “lead intoxication,” “EDTA” (MESH Term), “Ethylenedinitrilotetraacetic,” “edetic acid” (MESH Term), “succimer” (MESH Term), “Dimercaptosuccinic Acid,” along with their synonyms combined with Boolean operators. Inclusion criteria comprised studies involving adult populations aged >18 years, non-pregnant individuals, therapeutic research areas, systematic reviews/meta-analyses of randomised controlled trials or clinical trials, written in English, and with full-text availability. Exclusion criteria included articles with incomplete data or inaccessible full-text. Results: Based on the analysis of two reviewed literatures, the author obtained insights into the effectiveness of using DMSA compared to EDTA in cases of lead poisoning. DMSA can be administered orally, providing better chelation therapy efficacy than EDTA in treating lead poisoning. It effectively alleviates lead poisoning symptoms and reduces blood lead levels better than EDTA. Conclusion: DMSA can be considered an alternative chelating agent of choice for treating lead poisoning in workers. Keywords: Lead poisoning, Lead intoxication, EDTA, Ethylenedinitrilotetraacetic, succimer, Dimercaptosuccinic Acid.